2014
DOI: 10.1056/nejmoa1315878
|View full text |Cite
|
Sign up to set email alerts
|

Darapladib for Preventing Ischemic Events in Stable Coronary Heart Disease

Abstract: BackgroundElevated lipoprotein-associated phospholipase A 2 activity promotes the development of vulnerable atherosclerotic plaques, and elevated plasma levels of this enzyme are associated with an increased risk of coronary events. Darapladib is a selective oral inhibitor of lipoprotein-associated phospholipase A 2 . MethodsIn a double-blind trial, we randomly assigned 15,828 patients with stable coronary heart disease to receive either once-daily darapladib (at a dose of 160 mg) or placebo. The primary end p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
149
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(165 citation statements)
references
References 23 publications
8
149
1
Order By: Relevance
“…The STABILITY trial was a prospective double‐blind randomized trial evaluating the efficacy and safety of darapladib 160 mg, a specific inhibitor of Lp‐PLA 2 , compared with placebo concerning cardiovascular outcomes in patients with stable CHD 19. In brief, the study randomized 15 828 patients from 39 countries with stable CHD, defined as prior MI, prior coronary revascularization, or multivessel CHD confirmed by coronary angiography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The STABILITY trial was a prospective double‐blind randomized trial evaluating the efficacy and safety of darapladib 160 mg, a specific inhibitor of Lp‐PLA 2 , compared with placebo concerning cardiovascular outcomes in patients with stable CHD 19. In brief, the study randomized 15 828 patients from 39 countries with stable CHD, defined as prior MI, prior coronary revascularization, or multivessel CHD confirmed by coronary angiography.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in hypercholesterolemic diabetic swine17 and in an angiographic and intravascular ultrasound study in patients18 showed that darapladib prevented progression of the necrotic core, assumed to be the vulnerable component of atherosclerotic lesions. In the present STabilization of Atherosclerotic plaque By Initiation of darapLadIb TherapY (STABILITY) trial (ClinicalTrials.gov identifier NCT00799903), darapladib 160 mg daily did not significantly reduce the primary composite end point of cardiovascular death, myocardial infarction (MI), or stroke in patients with stable CHD (hazard ratio [HR] 0.94, 95% CI 0.85–1.03, P =0.20) but nominally reduced the rate of the secondary end point, major coronary events (coronary death, MI, or urgent coronary revascularization; HR 0.90, 95% CI 0.82–1.00, P =0.045) 19. The present predefined ancillary study evaluated the independent prognostic value of baseline Lp‐PLA 2 activity concerning cardiovascular events, the reduction of Lp‐PLA 2 activity by darapladib, and the associations between baseline and changes in Lp‐PLA 2 activity and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The design and main findings of the STABILITY trial were published previously 14. Briefly, STABILITY was a randomized, double‐blind, controlled trial that enrolled patients with a history of CHD, including previous myocardial infarction (MI), previous percutaneous coronary intervention or coronary artery bypass grafting, or multivessel coronary disease confirmed by angiography, and on statin therapy unless contraindicated or not tolerated.…”
Section: Methodsmentioning
confidence: 99%
“…The STABILITY (Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy) trial compared darapladib, an oral inhibitor of lipoprotein‐associated phospholipase A 2 , with placebo in patients with high‐risk stable CHD 14. This secondary analysis was planned to describe baseline characteristics, psychosocial factors, and treatments for CHD of men and women enrolled in this contemporary trial.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,9,10 However, there are several opinions about darapladib usefulness. 11 So, this study aims to determine epression of inflammation marker of T2DM in vivo model with darapladib treatment.…”
Section: Introductionmentioning
confidence: 99%